2020
DOI: 10.1093/gbe/evaa159
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Remodeling of the Cell Envelope in Bacteria of the Planctomycetes Phylum

Abstract: Bacteria of the Planctomycetes phylum have many unique cellular features, such as extensive membrane invaginations and the ability to import macromolecules. These features raise intriguing questions about the composition of their cell envelopes. In this study, we have used microscopy, phylogenomics and proteomics to examine the composition and evolution of cell envelope proteins in Tuwongella immobilis and other members of the Planctomycetes. Cryo electron tomography data indicated a distance of 45 nm between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 59 publications
3
16
0
Order By: Relevance
“…A massspectrometry analysis showed that this membrane layer contained beta barrel proteins, lipoproteins and proteins with cell surface motifs, homologs to which were uniquely identified in the SDS-soluble fraction in T. immobilis. We also observed pores in previous cell wall preparations of T. immobilis (Mahajan et al, 2020a). We therefore favor the hypothesis that the pore-containing membrane corresponds to the outer membrane, an interpretation that has also been suggested by others (Jogler et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…A massspectrometry analysis showed that this membrane layer contained beta barrel proteins, lipoproteins and proteins with cell surface motifs, homologs to which were uniquely identified in the SDS-soluble fraction in T. immobilis. We also observed pores in previous cell wall preparations of T. immobilis (Mahajan et al, 2020a). We therefore favor the hypothesis that the pore-containing membrane corresponds to the outer membrane, an interpretation that has also been suggested by others (Jogler et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with earlier findings showing that neither invaginated membranes nor DNA were observed early in the budding process (Santarella-Mellwig et al, 2013), but only at a later stage (Lee et al, 2009). As in a previous study using cryo electron tomography (Mahajan et al, 2020a), we observed a single, spherical particle of up to 400 nm in diameter in almost every cell. In the reconstructed and another, visually inspected, budding cell, the particle was only present in the mother cell.…”
Section: Fib-sem-based 3d-reconstruction Demonstrates Continuous But Heavily Invaginated Membrane Network In T Immobilissupporting
confidence: 93%
See 3 more Smart Citations